BERGURU PADA YOUTUBE: Menelaah Perilaku Budaya Komunitas Cover Dance Penggemar K-Pop - Utaminingrum, Kartika Ayu (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2016)
At the moment, the most widely discussed topic in Indonesia is the "Korean Wave" or Hallyu wave. Various fan bases appear followed by their respective characteristics. Fans have different ways to express their love for Korean art and culture. As one of the fastest-growing music genres in the world, Billboard Korea (2011) identified that K-pop gave birth to the latest global trend, namely K-pop cover dance. Cover dance comes as a form of expression of K-pop fans by prioritizing movements and dance to the music or rhythm. This article explains how Soulmate Community members adopted Korean culture through K-Pop cover dance, including knowledge about things related to South Korea after being hit by a message via YouTube, member attitudes towards matters related to South Korea as an effect of exposure to YouTube media messages, and what behaviors or actions are manifested as a result of learning South Korean culture through YouTube.